Effect of lysine acetylsalicylate on aluminium accumulation and (Na+/K+)ATPase activity in rat brain cortex synaptosomes after aluminium ingestion - Silva, V. S.
Aluminium is neurotoxic in humans and has been implicated in several neurological disorders. Chronic use of buffered aspirins, as aspegic, would likely constitute the major human aluminium uptake source. Low-dose aspirin is beneficial in secondary prevention of cardiovascular events, so it is widely used for long periods of time. We studied if oral administration of aspegic to rats modified the aluminium inhibitory effect on brain (Na+/K+)ATPase due to alteration in synaptosomal membrane aluminium content. Adult male Wistar rats were submitted to sub-acute (1.00 g/day during 10 days) and chronic (0.03 g/day during 4 months) dietary AlCl3 exposure and/or to aspegic (0.11 g/day). The exposure protocol increased the synaptosomal aluminium content especially after a long-term exposure to aluminium and aspegic. Although no alterations were observed in rat body weight gain and adenylate energy charge, the (Na+/K+)ATPase activity was significantly reduced when aluminium was orally administered to rats. The oral administration of aspegic increased the synaptosomal aluminium content and concomitantly enhanced the (Na+/K+)ATPase inhibition. In our exposure protocol the increase in synaptosomal aluminium content correlates with the reduction of the (Na+/K+)ATPase activity.